A course on web languages and web-based applications - Sridharan, K. (IEEE transactions on education, 2004)
With the growth in the popularity of the World Wide Web (WWW), there is a need to provide education and hands-on training to students in preparing materials for presentation on the Web, developing client and server-side software, and building Web-based applications. Employers seek candidates who are proficient in computer languages and tools used on the WWW. Courses on Web programming are in great demand. This paper presents the details of a course the author has developed on Web languages and Web-based applications. Key features of the course are 1) teaching of diverse Web languages and technologies using a program completion strategy, 2) discussion of Web-based applications involving database access and electrical/mechanical measuring instruments, and 3) long individual student projects and seminars.